Uganda : Technical Assistance Report-Implementing Fiscal Regimes for Extractive Industries: Technical Notes. (IMF Staff Country Reports; Country Report, 2017)
This Technical Assistance Report discusses the advice provided by the IMF staff to the authorities of Uganda regarding implementation of fiscal regimes for extractive industries. The report considers options on how to conduct future licensing rounds, including possible bid variables and bid evaluation methods. It provides detailed comments on the draft model Production Sharing Agreement, along with simulations of its fiscal terms. The report also explains how crude oil price into the refinery is likely to be a negotiated outcome using the pipeline tariff as a guide.